Exploration on traffic activities at the intersection and their impacts to the environment - Wahyuni, Mohd Shukeri Jamil (2016)
The problem of traffic system is first appeared at intersection. At intersection, there is often a lot of traffic activity such as stop and go condition, turn left or right and change lane that can lead to vehicle emission that. This study was conducted to assess the association of vehicle speed and volume to CO emission at the intersection. Then, level of CO emission was formulated based on vehicle speed and volume of vehicle. To achieve this study, two intersections have been choosing as a study area. By means of correlation and multiple regression analysis, the associations between speed and volume to the level of emission were established. A correlation analysis was conducted using Pearson’s R to determine the degree of association between speed and volume vehicle to CO emission. Traffic models were developed for the two of intersection evaluated in this work for morning, afternoon and evening peak periods at interval 15 minute every 2 hour during peak period. The models CO emission developed revealed that morning and evening peak produced strong relationship between speed and volume of vehicle towards CO emission at the intersection.